Quality management system in the company GVC Consultants according to ISO 9001:2015 - Yánez Flores, David Xavier; Perdomo Vélez, María García (Ingeniería Química y Desarrollo, 2024)
The objective of any organization is to obtain satisfied customers, which is based not only on the final service but on all the activities that directly and indirectly influence its performance. The planning, control and improvement of the processes involved is important because thanks to this the organization can minimize problems and add value to its activities. ISO 9001 in its 2015 version seeks to improve all processes of the organization, including internal and external parties that contribute to the development and delivery of the product or service. This makes it a perfect component for organizational restructuring and continuous improvement. This work designs a quality management system in GVC Consultants based on ISO 9001:2015. A diagnosis of the current situation is made, an improvement plan is proposed and the impact of the change towards a quality culture is measured. The diagnosis allows us to understand the organization and propose improvements. The implementation of the ISO 9001:2015 system seeks to restructure processes, involve the entire organization and instill a culture of continuous improvement. The expected result is to increase customer satisfaction through quality products and services.
Keywords: System; quality; organization; standard